La Llingua Asturiana: Distintividá, Identidá y Oficialidá/The Asturian Language: Distinctiveness, Identity, and Officiality, Corral-Esteban, A. (Ed.) (2025). Berlin, Bruxelles, Chennai, Lausanne, New York, Oxford: Peter Lang. 320 pp. - Álvarez-Sancho, Isabel (Lletres Asturianes, 2025)
Without abstract